Evaluation of systems of banana cultivation in the state of Mato Grosso do Sul, Brazil - Sandrini, Márcio; Cintra, Fernando Luís Dultra; Júnior, Ramão Ximenes (Pesquisa Agropecuaria Brasileira, 1991)
Systems of banana cultivation in the state of Mato Grosso do Sul, Brazil were evaluated with the objective of increasing the yield and to make this crop more profitable. The experiment was carried out in a clay soil and the testing cultivar was the Nanicão, Cavendish subgroup. The experimental design utilized was the randomized block design with four treatments and six replications. The employed treatmentes were: spacing of 3 m x 2 m without roguing, spacing of 3 m x 2 m with roguing, spacing of 2 m x 2 m with roguing, and spacing of 2 m x 2 m with roguing and mulching. The spacing system of 2 m x 2 m associated with the roguing practice and the use of plant residue as mulching produced the best banana yield per hectare, the highest weight of the first bunch and the highest weight of the banana fruit in the first cycle. The conventional spacing system (3 m x 2 m) associated with the roguing practice in the second cycle increased yield, weight of the first bunch, and fruit size.
Keywords: "Nanicão" cultivar; mulching; roguing; banana plant spacing; banana plant yield